A dual branch feature extraction network for heart sound signal analysis - Hao Chen; Wenye Gu (Scientific Reports)
Abstract The analysis of heart sound signals is critical in the early diagnosis of cardiovascular disease. However, the complexity and diversity of these signals pose significant challenges for accurate recognition. In this paper, we propose a novel heart sound dual-branch feature extraction network (HSDFE-Net) to address these challenges. The model first extracts both conventional audio features and bi-spectrum features from preprocessed heart sound signals, enabling comprehensive characterization of their linear spectral and nonlinear properties. Unlike conventional single-branch networks, HSDFE-Net employs a dual-branch architecture where one branch processes bi-spectrum features to capture nonlinear relationships, while the other processes conventional audio features. By fusing these complementary feature sets, the network achieves a more thorough understanding of signal characteristics. Furthermore, a squeeze-and-excitation module is integrated into the conventional audio branch to adaptively emphasize key feature channels, which enhances overall model performance. Experimental results on three public datasets demonstrate that HSDFE-Net achieves accuracies of 99.00%, 99.53%, and 83.33%, validating its effectiveness and robustness in heart sound analysis and providing a promising solution for heart sound recognition.